Pengaruh Pemanfaatan Media Audio Visual Dalam Pembelajaran Seni Tari Terhadap Hasil Belajar Pada Siswa Kelas XI SMA Darussalam Medan - DIAN RIDHAYANI (Universitas Negeri Medan, 2017)
This study discusses the Influence Use of Audio Visual Media in Learning Dance Of Learning Outcomes In High School Student Class XI Darussalam aims to describe the field and know the effect of the use of audio-visual media to the learning outcomes of students in dancing Ranup Lampuan in SMA Darussalam Medan. To discuss the purpose of the study above, use the theories related to the topic of this research is the theory of learning, learning theory, dance, theory of learning outcomes and audio-visual media. Time used in this study is for 2 (two) months, namely in July 2016 to August 2016. The study site is a Private School High School Darussalam Medan is located on the street. Darussalam No. 26 ABC, Petisah Medan, Medan, North Sumatra. The population in this study were high school Darussalam Medan, while samples were students of class XI IPA SMA Darussalam Medan. Analysis of the data in this study using quantitative descriptive, namely data collection techniques by observation, library research, assessment questionnaires, and documentation. The results based on the data collected can be seen that the ability of the students in learning the dance Ranup Lampuan class XI SMA Darussalam Medan before and after using audio-visual media obtained by the average value of 65.10 and 76.95. From these data it can be seen an increase in the value of before use and after use audio-visual media. Learning Dance Ranup Lampuan using audio-visual media positive and significant impact on learning outcomes of students of class XI SMA Darussalam Medan. Keywords : Audio-visual